Identity of wasp parasitoids (Hymenoptera) attacking Pieris brassicae (Linnaeus, 1758) (Lepidoptera: Pieridae) in South Africa - van Noort, Simon; Fernandez-Triana, Jose; Baur, Hannes; Shaw, Mark R (African Entomology, 2022)
The alien invasive large cabbage white, Pieris brassicae (Linnaeus, 1758) (Pieridae), although introduced into South Africa more than 27 years ago, has not dramatically expanded its distribution, possibly because it is effectively attacked by two parasitoid wasp species. Even though there is a cohort of parasitoid species associated with P. brassicae in the Northern Hemisphere, these are the only two recorded parasitoids in South Africa. We determine these parasitoid wasps as Cotesia glomerata (Linnaeus, 1758) (Braconidae: Microgastrinae) and Pteromalus puparum (Linnaeus, 1758) (Pteromalidae), and provide high resolution images and DNA barcodes to facilitate their recognition. This is the first record of C. glomerata from the Afrotropical region.